Analysis and Visualisation of Research Trends in Carbon Nano Tubes: A General Review - Kumar, Raman (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Carbon nanotubes are made up of carbon atoms, with each carbon atom covalently bonded to three other carbon atoms. The bibliometric analysis had been conducted to understand the active authors, organizations, journals, and countries involved in the research domain of “Carbon Nanotubes”. All published articles related to “Carbon Nanotubes” from “Scopus”, were analyzed using the VOS viewer to develop analysis tables and visualization maps.This article had set the objective to consolidate the scientific literature regarding the “Carbon Nanotubes”and also to find out the trends related to the same.The most active journals in this research domain were Journal of Computational and Theoretical Nano Science; Journal of Physical Society of Japan and Journal of Power Sourceswith the highest publications, citations, and co-authorship links. The most active countries were India and Japan. The leading organizations were the Chinese Academy of Sciences, China, and the Islamic Azad University of Iran.The most active authors who had made valuable contributions related to Nanomaterial were Li X, Ajiki H, and Ando T.